DAMPAK PEMBERIAN MEDIA LEAFLET DAN BERMAIN ULAR TANGGA TERHADAP PENINGKATAN PENGETAHUAN TENTANG CARA MENYIKAT GIGI - Intan Aritonang; Asmawati; Yenny Lisbeth Siahaan (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
The problem of dental caries is one of the most common health problems experienced by school-age children, so an understanding of good and correct tooth brushing and maintaining oral health must be instilled from an early age. This research aims to determine the impact of giving leaflet media and playing snakes and ladders on increasing knowledge about how to brush their teeth in students. This study used a quasy experiment method with a non-randomized pretest-posttest control group design. The research location was at SDN 065015 Medan Tuntungan Subdistrict. The research time started from January - May 2023. The subjects of this study were all third-grade students of SDN 065015 Medan Tuntungan District, totaling 30 people. The sample size was used as a total sampling of 30 people. The subjects of this study were divided into two groups, namely the intervention group of 15 people and the control group of 15 people. The intervention in this study was the provision of leaflet media and playing snakes and ladders. For the intervention and control groups, a pre-test was conducted before the subjects were given leaflet media and played snakes and ladders. Furthermore, both groups were given a post-test after being given leaflet media and playing Snakes and Ladders. Data collection was carried out by distributing questionnaires before and after being given leaflet media and playing snakes and ladders. Data analysis using paired t-test and unpaired t-test. The results showed that the average knowledge of students about how to brush their teeth in the intervention and control groups both experienced a significant increase in knowledge. There is a difference in the average score of students' knowledge before and after being given intervention through leaflet media and playing snakes and ladders (p = <0.05). To the teacher of SDN 065015 Medan Tuntungan to collaborate with the Puskesmas to provide socialization in the form of routine counseling to students about how to brush their teeth.